ENDOGENOUS SEX HORMONES LEVELS ARE ASSOCIATED WITH THE REVISED FRAMINGHAM STROKE RISK PROFILE IN POSTMENOPAUSAL WOMEN – A CROSS-SECTIONAL STUDY IN A SWEDISH COHORT. (June 2022) - Ottarsdottir, Kristin; Tivesten, Åsa; Li, Ying; Lindblad, Ulf; Hellgren, Margareta; Ohlsson, Claes; Daka, Bledar
Abstract : Objective: Levels of endogenous sex hormones in postmenopausal women have been associated with the risk of cardiovascular diseases. The aim of this study was to investigate the association between eight different endogenous sex hormones and the revised Framingham stroke risk profile (rFSRP) in Swedish postmenopausal women. Design and method: This is an observational cross-sectional study within the Vara Skövde cohort, a Swedish population-based study with the main focus on detecting hypertension and diabetes at an early stage. The participants in the present study were physically examined in 2002–2004, and endogenous sex hormones (-17-hydroxy progesterone, estrone, dihydrotestosterone (DHT), estradiol, dehydroepiandrosterone (DHEA), androstenedione, testosterone, and progesterone) were analyzed with a validated liquid chromatography-tandem mass spectrometry assay. Women 55 years old or older, with estradiol levels lower than 20 pg/mL, and non-users of hormonal therapy were included in the study (N = 146). Outcome variable was rFSRP, which estimates the individual´s 10-year risk of stroke based on blood pressure, smoking, atrial fibrillation, age, previous cardiovascular disease and diabetes status. Regression analyses of log-transformed rFSRP were fitted against sex hormones, adjusting for body mass index (BMI) or waist-to-hip ratio (WHR) (depending on which variable was more associated with hormone levels), C-reactive protein (CRP) and total cholesterol level. Results: Progesterone levels showed a positive association with rFSRP when adjusting for BMI. (18% increase in rFSRP per SD increase in progesterone, p = 0.020). Estrone was positively associated with rFSRP in the model adjusting for BMI (17 % increase in rFSRP per SD increase in estrone level, p = 0.020). Testosterone showed a positive association in the model adjusting for WHR (13 % increase in rFSRP per SD increase in testosterone, p = 0.019). Additional adjustments for CRP and cholesterol did not change the results for any of the hormones. No significant associations between other hormones and rFSRP were observed in this study. Conclusions: Increase in levels of estrone, testosterone and progesterone in postmenopausal women was associated with increase of rFSRP. Prospective studies are warranted for a better understanding of the importance of sex hormone levels for cardiovascular health in postmenopausal women.